Petromylidenes A–C: 2-Alkylidene Bile Salt Derivatives Isolated from Sea Lamprey (Petromyzon marinus) - Li, Ke (Mar Drugs, 2018)
Three novel bile acid derivatives, petromylidenes A–C (1–3), featuring uncommon alkylidene adductive scaffolds, were isolated from water conditioned with sexually mature male sea lampreys (Petromyzon marinus). Their structures were elucidated by mass spectrometry and NMR spectroscopy, and by comparison to spectral data of related structures. The identification of compounds 1–3, further illustrates the structural diversity of the 5α bile salt family. Compounds 1–3 exhibited notable biological properties as well, including high olfactory potencies in adult sea lampreys and strong behavioral attraction of ovulated female sea lampreys. Electro-olfactogram recordings indicated that the limit of detection for 1 was 10(−9) M, 2 was 10(−11) M, and 3 was less than 10(−13) M. These results suggested 1–3 were likely male pheromones, which guide reproductive behaviors in the sea lamprey.